TO THE BIOLOGY OF THE SNOW TROUT IN THE UPPER REACH OF THE CHIRCHIK RIVER (European Journal of Interdisciplinary Research and Development, 2023)
Males of the snow trout (Schizothorax curvifrons) in the upper reaches of the Chirchik River in Uzbekistan reach sexual maturity at the 2nd - 3rd year of life with a standard body length of 12 - 15 cm; females - in the 3rd - 4th year of life at 14 - 23 cm. Individual absolute fecundity is 6.6 - 71.5 thousand eggs. The coefficient of maturity of females before spawning was 5.48 - 17.5%. Yearlings reach an average standard length of 9.0 cm, two-year-olds - 13.9 cm, three-year-olds - 15.9 cm, four-year-olds - 21.7 cm, five-year-olds - 24.8 cm.